SUSTAINABLE CITIES AND COMMUNITIES: URBAN PLANNING AND DEVELOPMENT STRATEGIES - Shoh-Jаkhon Khаmdаmov; Anvar Usmanov (Journal of Artificial Intelligence and Digital Economy, 2024)
This paper explores the concept of sustainable cities and communities, emphasizing the importance of urban planning and development strategies in achieving sustainable urban growth. It discusses the challenges faced by urban areas, such as rapid population growth, environmental degradation, and socio-economic inequalities. The paper presents key strategies for sustainable urban development, including smart city technologies, green infrastructure, inclusive housing policies, and community engagement. It also highlights the role of governance and policy frameworks in supporting sustainable urban development. By implementing comprehensive urban planning and development strategies, cities can become more livable, resilient, and inclusive